Multi-Detector CT Enterography to detect jejunal angiodysplasia: challenging cause of gastrointestinal bleeding - Runza, Giuseppe; Barbiera, Filippo; Maffei, Erica; Punzo, Bruna; Cavaliere, Carlo; Cademartiri, Filippo (Acta Biomedica Atenei Parmensis, 2021)
The small bowel angiodysplasia is a rare cause of intestinal bleeding. Usually, the diagnosis is performed with selective conventional angiography. We report a case of 73-year-old man, who was hospitalized after recurrent episodes of melena and anaemia. MDCT-enterography performed before and after intravenous administration of contrast medium, detected an increased density area which was confirmed to be a jejunal angiodysplasia.